Pengaruh Currency Dan Co-Creation Terhadap Customer Loyalty Yang Dimediasi Oleh Customer Satisfaction - Wibowo, Bima Ardiyanto; Kurniawan, Mateus Andhi; Mujanah, Siti; Fianto, Achmad Yanu Alif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Customer satisfaction is one of the key drivers of customer loyalty, both for products and services. This study investigates the influence of service quality, brand image, and cost on customer satisfaction, as well as whether customer satisfaction serves as an effective mediator. The research surveyed general patients of Tritya Eye Clinic Surabaya. Sampling was conducted using a purposive sampling method with specific considerations, resulting in 154 respondents. The data were analyzed using Structural Equation Modelling (SEM). The findings indicate that service quality, brand image, and cost contribute positively to customer satisfaction. The study also confirms that customer satisfaction mediates the relationship between service quality, brand image, and cost with customer loyalty. This research contributes to understanding operational management by applying the framework of service quality, brand image, and cost in the context of healthcare service providers.